Analysis of the use of Learning Management System (LMS) Platforms to Enhance the Competencies of Civil Servants in the Human Resource Development Agency of East Java Provincial Government - Khakim, M. Azizul; Chaerussalaeh, Heru; Rahayu , Sri (SEAN Institute, 2024)
Competence is essential in forming attitudes and behaviors that contribute to achieving superior performance. This has prompted the Human Resource Development Agency of the East Java Provincial Government to develop the L-Bos Learning Management System platform to enhance the competencies of Civil Servants (ASN) in East Java. This study intends to examine how utilizing the LMS affects platform on the competencies of ASN within the Human Resource Development Agency of the East Java Provincial Government. The research employs a qualitative method with descriptive qualitative methods of analysis. Methods of gathering data include observations and interviews. The findings reveal that the implementation of LMS satisfies the metrics for perceived utility and usability, effectively enhancing the competencies of civil servants in East Java Province.